Characteristics of Fruit Leather with Proportion of Carica Puree (Carica pubescens) : Lime Juice (Citrus aurantifolia) and Carrageenan and Their Shelf Life Estimation - Muslimah, Yeny Andrea; Rosida, Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Fruit leather is a delectable treat crafted from pureed and dehydrated fruit. Carica fruit (Carica pubescens) contains fiber and pectin, which are requirements for making fruit leather. Lime (Citrus aurantifolia) was added as an acid in the gel formation. The addition of carrageenan is expected to improve the plasticity of fruit leather. One of the qualities of fruit leather is determined by its shelf life. This study seeks to assess the physicochemical and organoleptic attributes of carica and lime fruit leather, as well as to analyze the estimation of shelf life resulting from the optimal treatment. Factorial completely randomized design (CRD) with two factors was utilized in the study. Factor I involved the ratio of carica puree to lime juice (95:5, 90:10, 85:15), while factor II consisted of different carrageenan concentrations (0,3%, 0,6%, 0,9%) with two replications. The results were documented in English. The data was subjected to analysis of variance (ANOVA) followed by Duncan's New Multiple Range Test (DNMRT) at a significance level of 5%. The most effective treatment was found to be a blend of 95% carica puree to 5% lime juice, combined with 0.9% carrageenan. The test results revealed a moisture content of 15,33%, crude fiber content of 2,55%, pH level of 4.65, tensile strength of 4,45 N, vitamin C concentration of 12,20 mg/100g, antioxidant activity of 25,23%, color intensity of 3,24 (neutral), aroma profile of 3,04 (neutral), taste rating of 4,00 (like), texture score of 3,12 (neutral), total dietary fiber content of 4,45%, and an estimated shelf life of 70 days at 10?C (under refrigeration), 10 days at 30?C (at room temperature), and 3 days at 50?C.